Kraft lignin solubility and its chemical modification in deep eutectic solvents - Sosa, Filipe H. B. (2022)
Lignin stands as a promising raw material to produce commodities and specialty chemicals, yet its poor solubility remains a big challenge. Recently, deep eutectic solvents (DES) have been proposed as sustainable solvents with high potential to dissolve and valorize lignin. In the present study, the ability of DES based on cholinium chloride ([Ch]Cl) combined with alcohols and carboxylic acids as hydrogen bond donors (HBDs) to dissolve kraft lignin and to change its chemical structure was examined. The influence of the chemical nature of HBDs, water content, and HBD:hydrogen bond acceptor (HBA) molar ratio on the solubility of kraft lignin in DES was studied (313.15 K). The kraft lignin solubility was enhanced by increasing both the HBD’s carbon chain length and the molar ratio, with [Ch]Cl:HEXA (1,6-hexanediol) and [Ch]Cl:MaleA (maleic acid) being the best studied solvents for kraft lignin dissolution, while the addition of water was a negative factor. The thermal treatments (393.15 K) of kraft lignin show that carboxylic acid-based DES promote chemical modifications to kraft lignin, including the disruption of several C–O covalent type bonds (e.g., β-O-4, α-O-4 and α-O-α), while alcohol-based DES were found to be nonderivatizing solvents maintaining the lignin chemical structure. These results show the versatility of DES, which, depending on their chemical nature, may offer distinct strategies for lignin valorization.